Elevated Serum Human Cytomegalovirus IgM Levels in the Acute Phase of Ischemic Stroke are Associated with Increased Risk of Death and Major Disability - Zhang, Chenhuan; Huang, Ping; Zhang, Peipei; Zhou, Mo; Gao, Ya; Zhang, Yonghong; Guo, Yumei; Lv, Liying; Xu, Tan (Current Neurovascular Research, 2018)
Background: There was a lack of studies on the association between Human Cytomegalovirus (HCMV) infection and prognosis of ischemic stroke, although it was indicated that human cytomegalovirus DNA has played a role in several cardiovascular disorders. Objective: To examine the association between HCMV IgM levels in the acute phase and death and major disability after 2 weeks of acute ischemic stroke. Methods: Serum HCMV IgM levels were measured in 1150 participants in China. Study outcome data on major disability and combined outcome of death and major disability were collected at 2 weeks after stroke onset or hospital discharge. Results: After 2 weeks of follow-up, 351 participants (30.52%) suffered from a major disability or died. Serum HCMV IgM was correlated with the combined outcome of death and major disability significantly after adjustment confounding factors. For example, the highest quartile of HCMV IgM was related to an odds ratio (95% confidence interval) of 1.84 (1.12-3.11) for the combined outcome. Risk prediction of the combined outcome was improved by the addition of serum HCMV IgM to conventional risk factors (net reclassification index 25.41%, p = 0.0002; integrated discrimination improvement 0.70%, p = 0.04377). Conclusions: Elevated serum HCMV IgM levels in the acute phase of ischemic stroke were correlated with increased risk of combined outcome of death and major disability, indicating that serum HCMV IgM could be an important predictive factor for poor prognosis of ischemic stroke.
Keywords: prognosis